Exploring Design and Security Perception on Digital Payment Adoption Among the Z Generation in Indonesia - Aldilla Iradianty (AIBPM Publisher, 2021)
The adoption of digital payments in Indonesia during the COVID-19 pandemic increased, this study will discuss the factors that influence the Z generation in the intention to use digital payment applications and effect from design and security beside TAM 3 model, because this generation is close to the digital world, through this research, we will know using SEM-PLS software with the number of respondents is 138 Z generation spread throughout Indonesia. It was found the direct influence of design and security on perceived ease of use and perceived usefulness has an effect, while other direct effects are not significant (perceived ease of use, perceived usefulness, security on customer intention to use, and perceived ease of use on perceived usefulness). So, the digital payment application development company can develop more related to the design factor and the security level so that the Z generation can use digital payment applications more often.